Elevated total cholesterol in healthy adults mediates the association between impaired thyroid hormone sensitivity and hyperuricemia - Huang, Xiying; Yu, Daojun (Frontiers in Endocrinology, 2025)
PurposeThis study aims to explore the association between impaired thyroid hormone sensitivity and hyperuricemia, and to analyze the potential mediating role of total cholesterol (TC), thereby providing a new theoretical basis for the early prevention and intervention of hyperuricemia.MethodsThis study utilized health check-up data from Health Examination Management Center of the second affiliated hospital of Zhejiang University School of Medicine, collected between 2019 and 2020. The dataset included 80568 participants with normal thyroid function, no family history of thyroid disorder, and no history of thyroid hormone or lipid-lowering medication use. The extent of impaired thyroid hormone sensitivity was assessed using thyroid hormone sensitivity indices, such as the Thyroid Feedback Quantile Index (TFQI), Parameter Thyroid Feedback Quantile Index (PTFQI), Thyroid Resistance Index (TT4RI), and Thyroid Stimulating Hormone Index (TSHI). Logistic regression models were employed to analyze the relationship between thyroid hormone sensitivity indices and hyperuricemia, while mediation analysis was conducted to quantify the mediating effect of total cholesterol.ResultAmong the 22843 participants, 6597(28.88%) were diagnosed with hyperuricemia. The thyroid hormone sensitivity indices (TFQI, PTFQI, TT4RI, and TSHI) were notably elevated in the hyperuricemia group compared to the non-hyperuricemia group (P<0.001). A dose-response relationship was observed between thyroid hormone sensitivity indices and hyperuricemia, and this association remained noticeable after adjusting for factors such as age, gender, BMI, hypertension, and diabetes. Mediation analysis indicated that total cholesterol significantly mediated the association between impaired thyroid hormone sensitivity and hyperuricemia, with a mediation proportion ranging from6.89% to 18.42%.ConclusionThis study is the first to uncover a new relevance by which impaired thyroid hormone sensitivity mediates hyperuricemia through total cholesterol. This finding provides fresh epidemiological evidence for the interplay between thyroid dysfunction and hyperuricemia and suggests that monitoring thyroid hormone sensitivity indices in high-risk populations for hyperuricemia might be conducive in early risk stratification. Moreover, lipid-lowering treatment in subclinical thyroid dysfunction patients may simultaneously enhance uric acid metabolism, offering creative insights for the precise prevention and management of hyperuricemia.